Moving Ethiopian smallholder dairy along a sustainable commercialization path: missing links in the innovation systems - Lemma, T.; Tegegne, Azage; Puskur, Ranjitha; Hoekstra, Dirk (Addis Ababa University, 2008)
Ethiopian needs to achieve accelerated agricultural development along a sustainable commercialization path to alleviate poverty and ensure overall national development. In this regard, sustainable commercial of smallholder dairying provides a viable and growing opportunity; with deliberate, appropriate and sustained policy support. A recent empirical analysis concludes however, that Ethiopian smallholder dairy sub-sector has not been able to take-off despite decades of development interventions. The current paper looks into this paradox of Ethiopian smallholder dairy development; identifies and discusses the implications of emerging opportunities and challenges for the sub-sector development; and explores strategic options for the sub-sector take-off. This paper argues that the impact of the decades of efforts for the sub-sector developments have been hampered, among others, by disconnects in the dairy innovation systems. There are missing/weak linkages between diverse knowledge sources, technological and non-technological innovations, development interventions and local context, production and market, R&D services and development challenges, public and private efforts, and between policymaking and development practice. Some strategic options are identified along with implementation modalities. The recommendations forwarded to get Ethiopian smallholder dairying moving along a sustainable commercialization path encompass: improving economic incentives to encourage innovation; organizing dairy producers and linking them with vertically coordinated value chain; pursuing holistic approach to achieving sustainable technological innovation to increase supply response; supporting private sector development and promoting public-private partnership, creatively using the expanding ICT infrastructure as a means for facilitating multi-stakeholder interaction and knowledge management; formulating appropriate and adaptive policy for the sub-sector development; along with complementary national strategy capable of providing clear roadmap; guiding spatially targeted investment and intervention decisions; and defining principles for pragmatic participation, inter-organizational interaction and coordination. Finally, strengthening commodity-based local - woreda/milkshed- innovation systems capacity with value chain perspective is underlined. The later provides a practical option to stimulating process-driven collective experiential learning for achievement of better impact through continuous incremental improvement/innovation, and facilitates scaling up and-out of successful experiences to achieve wider socio-economic impact and inform policymaking.